2019
DOI: 10.1038/s41598-019-52248-9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that fodipir (DPDP) binds neurotoxic Pt2+ with a high affinity: An electron paramagnetic resonance study

Abstract: Oxaliplatin typically causes acute neuropathic problems, which may, in a dose-dependent manner, develop into a chronic form of chemotherapy-induced peripheral neuropathy (CIPN), which is associated with retention of Pt2+ in the dorsal root ganglion. A clinical study by Coriat and co-workers suggests that co-treatment with mangafodipir [Manganese(II) DiPyridoxyl DiPhosphate; MnDPDP] cures ongoing CIPN. These authors anticipated that it is the manganese superoxide dismutase mimetic activity of MnDPDP that explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 37 publications
(74 reference statements)
1
17
0
Order By: Relevance
“…However, such an effect will only be transient and would not fix the ultimate cause of chronic Pt 2+ -associated CIPN, namely retention of Pt 2+ in the DRG. The fact that Pt 2+ binds fodipir and PLED with high affinity, as shown in our recent work [2], provides, in our opinion, a more plausible explanation for the therapeutic effects of mangafodipir and calmangafodipir as suggested by Coriat and co-workers [11] and Glimelius and co-workers in patients with chronic oxaliplatin-associated CIPN [12]. The situation in acute cellular stress as those seen in ischemia-reperfusion injury, doxorubicin-induced cardiac toxicity, paracetamol (acetaminophen)-induced liver toxicity and chemotherapy-induced myelosuppression is quite different where the combined MnSOD-mimetic and iron-chelating activity of mangafodipir and calmangafodipir most probably explains the therapeutic effects of these compounds [13].…”
supporting
confidence: 70%
See 2 more Smart Citations
“…However, such an effect will only be transient and would not fix the ultimate cause of chronic Pt 2+ -associated CIPN, namely retention of Pt 2+ in the DRG. The fact that Pt 2+ binds fodipir and PLED with high affinity, as shown in our recent work [2], provides, in our opinion, a more plausible explanation for the therapeutic effects of mangafodipir and calmangafodipir as suggested by Coriat and co-workers [11] and Glimelius and co-workers in patients with chronic oxaliplatin-associated CIPN [12]. The situation in acute cellular stress as those seen in ischemia-reperfusion injury, doxorubicin-induced cardiac toxicity, paracetamol (acetaminophen)-induced liver toxicity and chemotherapy-induced myelosuppression is quite different where the combined MnSOD-mimetic and iron-chelating activity of mangafodipir and calmangafodipir most probably explains the therapeutic effects of these compounds [13].…”
supporting
confidence: 70%
“…The authors conclude that their study lends mechanistic support that mangafodipir and calmangafodipir exert the neuroprotective effects through their manganese superoxide dismutase (MnSOD)-mimetic and iron chelating activities, in relation to oxaliplatin-associated chemotherapy-induced peripheral neuropathy (CIPN). As authors of a recently published, but by the authors of the current article non-cited, article [ 2 ], we would like to make some essential comments. Our article suggests another and, in our opinion, more plausible mechanism behind the efficacy of these compounds, in this particular case, namely that the chelator part of mangafodipir, fodipir or its dephosphorylated metabolite PLED (diPyridoxyL EthylDiamine), binds and increases renal excretion of Pt 2+ by a process known as chelation therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The probable mechanism of PIPN development is via retention of Pt 2+ ions in the dorsal root ganglion and where they can bind to proteins, that lead to the development of oxidative and nitrosative stress [ 102 ]. In the recent study of Stehr et al [ 88 ] was shown that Pt 2+ has an affinity for DPDP, and the newly formed complex of metal with DPDP has fast excretion and low toxicity which are positive aspects for use of DPDP as chelation therapy of PIPN. Another chelation complex of manganese and the ligand fodipir, mangafodipir, displayed significant results in the study conducted by Coriat et al [ 89 ] on oxaliplatin-induced neurotoxicity in a mouse model as well as in patients with oxaliplatin neuropathy (grade ≥2).…”
Section: Antioxidants In the Treatment Of Platinum-based Chemothermentioning
confidence: 99%
“…These benefits were partly explained by acute MnSOD mimetic actions. Another likely mechanism implies chelation and elimination of oxidizing metals including platinum ions (Pt 2+ ) released from oxaliplatin, an interpretation supported by EPR analysis revealing a Pt 2+ affinity to DPDP close to that of Cu + [ 92 ]. With an accumulated MnDPDP dose up to 40 μ mol/kg over 4 months in Coriat's study, plasma Mn ( Figure 14(c) ) rose gradually without exceeding normal levels [ 33 ].…”
Section: Therapy In Humansmentioning
confidence: 99%